2020
DOI: 10.4103/2452-2473.297461
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal midazolam sedation as an effective sedation route in pediatric patients for radiologic imaging in the emergency ward: A single-blind randomized trial

Abstract: OBJECTIVES: Prevention and reduction of pain, anxiety, and fear during medical procedures is one of the most important factors that should be considered in pediatric emergencies. The aim of this study was to compare the efficacy of oral versus intranasal midazolam in sedation during radiologic imaging in the largest province of Iran, Kerman. MATERIALS AND METHODS: Eighty children were enrolled in this single-blind clinical trial based on convenience sampling and were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…From the analysis of 10 studies, 2,[19][20][21][22][23][24][25][26][27] we observed that Propofol, in monotherapy, has been effective for this purpose with bolus from 1 to 2 mg/kg, with an average maintenance of 100 mcg/kg/min. 19,20 Most commonly described adverse effects were desaturation, laryngospasm and hypotension.…”
Section: Sedation For Imaging Examsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the analysis of 10 studies, 2,[19][20][21][22][23][24][25][26][27] we observed that Propofol, in monotherapy, has been effective for this purpose with bolus from 1 to 2 mg/kg, with an average maintenance of 100 mcg/kg/min. 19,20 Most commonly described adverse effects were desaturation, laryngospasm and hypotension.…”
Section: Sedation For Imaging Examsmentioning
confidence: 99%
“…Lam, 2018 2 Malia, 2018 24 Cossovel, 2022 26 Mayel, 2020 25 Sayed,2022 20 Midazolam IN ou VO: 0,2 -1 mg/kg Consider for premedication. When in association, it was related to higher latency and longer time until awakening.…”
Section: First Author Publication Year Drug Dose Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diverse medications have been proposed as a premedication to alleviate children's anxiety and facilitate their separation from their parents [2] . The optimal premedication for children must be readily acceptable, have a rapid and dependable onset, and have minimal adverse effects [3] . Aerosolized medications may facilitate enhanced absorption via the nasal, oral, and respiratory mucous membranes, with advantage of better acceptability by the patient [4] .…”
Section: Introductionmentioning
confidence: 99%